Plasma membrane topography governs the 3D dynamic localization of IgM B cell antigen receptor clusters. (3rd January 2023) - Saltukoglu, Deniz; Özdemir, Bugra; Holtmannspötter, Michael; Reski, Ralf; Piehler, Jacob; Kurre, Rainer; Reth, Michael
Abstract: B lymphocytes recognize bacterial or viral antigens via different classes of the B cell antigen receptor (BCR). Protrusive structures termed microvilli cover lymphocyte surfaces, and are thought to perform sensory functions in screening antigen‐bearing surfaces. Here, we have used lattice light‐sheet microscopy in combination with tailored custom‐built 4D image analysis to study the cell‐surface topography of B cells of the Ramos Burkitt's Lymphoma line and the spatiotemporal organization of the IgM‐BCR. Ramos B‐cell surfaces were found to form dynamic networks of elevated ridges bridging individual microvilli. A fraction of membrane‐localized IgM‐BCR was found in clusters, which were mainly associated with the ridges and the microvilli. The dynamic ridge‐network organization and the IgM‐BCR cluster mobility were linked, and both were controlled by Arp2/3 complex activity. Our results suggest that dynamic topographical features of the cell surface govern the localization and transport of IgM‐BCR clusters to facilitate antigen screening by B cells. Synopsis: Combination of volumetric, high‐speed microscopy with custom 4D image analysis shows that the Ramos B lymphocyte surface is composed of elevated topographical features organized in a dynamic network‐like pattern. IgM‐class B cell antigen receptors (IgM‐BCR) form clusters that are coupled to the 3D structures on the cell surface. The surface of resting Ramos B‐cell harbors a dynamic network of elevated ridges that interconnects neighbouring microvilli. IgM‐BCR clusters are associated with ridges and microvilli with the highest density at the highly curved segments connecting these two structures. Dynamics of IgM‐BCR clusters and ridges are both controlled by Arp2/3 complex activity. The association of IgM‐BCR clusters with elevated surface structures is governed by factors upstream of the actin cytoskeleton. Abstract : High‐resolution microscopy of the Burkitt's lymphoma Ramos B cell line reveals that dynamic topographical features of the cell surface govern plasma membrane localization of the B cell receptor upstream of actin and microtubule cytoskeleton.